2021
DOI: 10.21608/ejfs.2021.45938.1082
|View full text |Cite
|
Sign up to set email alerts
|

Impact of incorporation of Monechma ciliatum seed flour on the chemical composition, nutritional value and sensory evaluation of sorghum Kisra

Abstract: M onechma ciliatum (MC) seeds are a rich plant source of protein, fat, minerals, and other essential nutrients. The current study aims to investigate the impact of using MC seeds as a plant-based food supplement on kisra (Sudanese bread made of sorghum flour). To obtain the most benefits from the MC, seeds were subjected to three treatments, boiling, roasting, and germination. The raw and treated MC seeds were separately ground and added to sorghum flour with ratio of 1:10 each. The common kisra made of pure s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Crude ash and crude protein ratios of sweet sorghum seeds showed great differences between varieties; While the highest crude ash and crude protein ratios were obtained in Erdurmuş and Gülşeker cultivars, respectively, the lowest crude ash and crude protein rates were found in Cowley and Sorge cultivars. In the researches on the raw ash and crude protein contents of sorghum; the crude ash and crude protein ratios were obtained as 1.4-1.6% and 12.1-14.1%, respectively, in sorghum hybrid grains (Isa 2009), as 5.9-9.1% and 18.6-25.2%, respectively, in different sorghum varieties forage (Zhapayev et al 2015), as 4.8% and 5.1%, respectively, in Ceres-81 sweet sorghum variety (Macedo et al, 2017), as 1.03-2.94% and 10.90-14.97%, respectively, in sorghum grain (Ebadi et al 2019), as 1.57% and 11.58%, respectively, in Kisra sorghum cultivar (Mustafa et al 2021).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Crude ash and crude protein ratios of sweet sorghum seeds showed great differences between varieties; While the highest crude ash and crude protein ratios were obtained in Erdurmuş and Gülşeker cultivars, respectively, the lowest crude ash and crude protein rates were found in Cowley and Sorge cultivars. In the researches on the raw ash and crude protein contents of sorghum; the crude ash and crude protein ratios were obtained as 1.4-1.6% and 12.1-14.1%, respectively, in sorghum hybrid grains (Isa 2009), as 5.9-9.1% and 18.6-25.2%, respectively, in different sorghum varieties forage (Zhapayev et al 2015), as 4.8% and 5.1%, respectively, in Ceres-81 sweet sorghum variety (Macedo et al, 2017), as 1.03-2.94% and 10.90-14.97%, respectively, in sorghum grain (Ebadi et al 2019), as 1.57% and 11.58%, respectively, in Kisra sorghum cultivar (Mustafa et al 2021).…”
Section: Resultsmentioning
confidence: 99%
“…In the study examining the effects of plant growth regulators on the nutritional values of sweet sorghum, it was reported that the NDF ratios of Cerse-81 sweet sorghum variety ranged from 42.7-73.2 g/kg DM (Macedo 2017). On the other hand, crude fiber ratios were obtained as 2.0-2.7% in sorghum hybrid grain (Issa 2009), as 2.0-2.7% in sorghum grain (Vila-Real et al, 2017), as 1.98-8.99% in different varieties of sorghum kernels (Ebadi et al 2019), and as 1.68% in Kisra sorghum variety (Mustafa et al 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Many studies have been conducted to validate the traditional uses of the different parts of the plants. As M.ciliatum seeds are previously known as a rich source of protein, fat, minerals and other essential nutrients, Mariod, et al [19] conducted a study to evaluate the impact of M. ciliatum. The focus of this study was on these seeds as a plant -based supplement on sorghum kisra (Sudanese bread made of sorghum flour(as a stable diet for most of Sudanese population.…”
Section: Chemical Composition and Nutritional Value Of M Ciliatummentioning
confidence: 99%
“…16 In Sudan, it is cultivated in western and south-western regions and is locally named black mahlab or El-Mahlab El-Aswad due to it being a small brownish-black seed. [17][18][19] The seeds are widely used as a traditional medication for general body pain, liver, cold, diarrhoea, and sterility in women and food supplements. [20][21][22] The seeds powder is also employed in traditional Sudanese fragrances, lotions, and other cosmetics used for wedding preparation.…”
Section: Introductionmentioning
confidence: 99%
“…Monechma ciliatum belongs to Acanthaceae and it is a well‐known pharmaceutical plant that grows in some regions of arid and semi‐arid parts of tropical Africa 16 . In Sudan, it is cultivated in western and south‐western regions and is locally named black mahlab or El‐Mahlab El‐Aswad due to it being a small brownish‐black seed 17–19 . The seeds are widely used as a traditional medication for general body pain, liver, cold, diarrhoea, and sterility in women and food supplements 20–22 .…”
Section: Introductionmentioning
confidence: 99%